Efforts to Increase the Cognitive and Physical Abilities of Kindergarten Students - Herman Tarigan; Boy Sembaba Tarigan; Dody Tri Iwandana (UNIVERSITAS NEGERI MAKASSAR, 2023)
Physical education in general is part of education. Through physical education is hoped that individual development is not only beneficial for improving psychomotor abilities, but also for cognitive and affective development, so that physical education contributes significantly to the development of all children. One form of formal education is through physical education at kindergarten. Which is part of overall education, aiming to develop aspects of physical fitness, movement skills, critical thinking skills, social skills, reasoning, emotional stability, moral action, aspects of a healthy lifestyle, and the introduction of a clean environment. The purpose of this study was to improve the cognitive and physical abilities of kindergarten students through rotating ring games at PKK Wates Bumiratu Nuban Kindergarten, Central Lampung and to improve children's learning outcomes, teachers must be skilled in teaching and also master the subject matter. The learning process requires good teaching skills because physical education learning needs movement skills and an approach model in its implementation. This type of research is classroom action research with three cycles and each cycle has different activities. The sample used in this study was a group of 32 TK PKK Wates Bumiratu Nuban Group B. Data collection in each cycle used an instrument for assessing the cognitive and physical abilities of kindergarten children. Data analysis technique using tabulation and proportion. The results of this study indicate that there is an increase in each cycle, namely: the first cycle of 25%, the second cycle of 31.25%, and the third cycle of 43.75%. Based on the analysis and discussion of the research results, it can be concluded as follows: Learning by using rotating ring games can improve the cognitive and physical abilities of the children of Group B PKK Wates Bumiratu Nuban Lampung. Learning with rotating ring games is very effective as a model of an educational approach to learning and playing for children's cognitive and physical abilities.